Substrate Noise Coupling in RFICs - Helmy, Ahmed (Springer, 2017)
Substrate Noise Coupling in RFICs addresses substrate noise coupling in RF and mixed signal ICs when used in a system on chip (SoC) containing digital ICs as well. This trend of integrating RF, mixed signal ICs with large digital ICs is found in many of today's commercial ICs such as single chip Wi-Fi or Bluetooth solutions and is expected to grow rapidly in the future. The book reports modeling and simulation techniques for substrate noise coupling effects in RFICs and introduces isolation structures and design guides to mitigate such effects with the ultimate goal of enhancing the yield of RF and mixed signal SoCs . This is particularly critical when process feature sizes scale down to the nano meter range.